Cyberbullying Detection using Machine Learning from Social Media comments in Bangla Language - Tuhin, Saikat Halder; Islam, MD Touhidul; Islam, MD. Tauhidul (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.